The Harawayan Bee Hotel: a tool to catalyse emancipatory change within and beyond the Education for Sustainable Development agenda in pre-service teacher training - Marco Bernardini; Jo Anna Reed Johnson (Global Social Challenges Journal)
The notion of the Anthropocene has become a popular (and contested) term to describe the times we live in; among other things, it alerts us to the damage mainstream Western-centred anthropocentrism has wreaked on nature: in so doing, the Anthropocene signals that for life as we know it to continue, a more sustainable relationship with nature must be urgently implemented. The article will discuss a project that emerged as part of a teacher education programme in the UK where selected insights elaborated by Donna Haraway have been used to inform a Bee Hotel project. The resulting ‘Harawayan’ Bee Hotel (HBH) was used as a catalyst to help trainee teachers to both blend climate education into the standard curriculum to be delivered during their placements and, importantly, to introduce them to a new conceptualisation of nature. Specifically, trainee teachers were presented with, and encouraged to integrate into their teaching practices, a vision of nature that recognises and respects its uniqueness, agency and worth, and that accepts that some level of ecological instrumentalisation and destruction is necessary for human life. The article will argue that the HBH acts as a microcosm where it is possible to forge and practice, for both present and future generations, an ethics that encourages the establishment of a respectful relationship with nature, facilitating the meeting of SDGs and offering the thinking tools to go beyond them.